A comprehensive review on the implications of Yogic/Sattvic diet in reducing inflammation in type 2 diabetes - Anupama Vallazhath; Pooja Yedehalli Thimmappa; Harshit B. Joshi; Krishna Raghava Hebbar; Anupama Nayak; Shashikiran Umakanth; Apar Avinash Saoji; Nandi Krishnamurthy Manjunath; Basavaraj S. Hadapad; Manjunath B. Joshi (Nutrition & Diabetes)
Abstract Chronic inflammation in type 2 diabetes (T2D), characterized by constitutively activated immune cells and elevated pro-inflammatory mediators along with hyperglycaemia and increased free fatty acids and branched chain amino acid levels, significantly alters the immuno-metabolic axis. Over the years, dietary intervention has been explored as an effective strategy for managing T2D. Evidence from experimental and clinical studies indicates that various diets, including Mediterranean, Nordic, Palaeolithic and ketogenic diets, increase insulin sensitivity, decrease gluconeogenesis, and adiposity, and exert anti-inflammatory effects, thus preserving immuno-metabolic homeostasis in individuals with T2D. Indian dietary sources are categorized as Sattvic, Rajasic, and Tamasic, depending on their impact on health and behaviour. The Yogic diet, commonly recommended during yoga practice, is predominantly Sattvic, emphasizing plant-based whole foods while limiting processed and high-glycaemic-index items. Yogic diet is also recommended for Mitahara, emphasizing mindful eating, which is attributed to calorie restriction. Adopting a Yogic diet, featuring low-fat vegetarian principles, strongly reduces inflammatory mediator levels. This diet not only ameliorates insulin resistance and maintains a healthy body weight but also regulates immunomodulation, enhances gut microbiome diversity and provides essential phytonutrients, collectively preventing inflammation. Although, preliminary studies show aforementioned beneficial role of Yogic diet in improving diabetes associated metabolic and inflammatory changes, precise cellular and molecular mechanisms are not yet understood. Hence, further studies are warranted to decipher the mechanisms. This review summarizes the multiple roles of Yogic diet and related dietary components in mitigating inflammation and enhancing glycaemic control in T2D.